Enrichment and characterization of ferritin for nanomaterial applications. (14th December 2015) - Ghirlando, Rodolfo; Mutskova, Radina; Schwartz, Chad
Abstract: Ferritin is a ubiquitous iron storage protein utilized as a nanomaterial for labeling biomolecules and nanoparticle construction. Commercially available preparations of horse spleen ferritin, widely used as a starting material, contain a distribution of ferritins with different iron loads. We describe a detailed approach to the enrichment of differentially loaded ferritin molecules by common biophysical techniques such as size exclusion chromatography and preparative ultracentrifugation, and characterize these preparations by dynamic light scattering, and analytical ultracentrifugation. We demonstrate a combination of methods to standardize an approach for determining the chemical load of nearly any particle, including nanoparticles and metal colloids. Purification and characterization of iron content in monodisperse ferritin species is particularly critical for several applications in nanomaterial science.